THE IMPLEMENTATION OF ONLINE MATHEMATICS GAMES TO IMPROVE MATHEMATICAL REPRESENTATION ABILITY OF JUNIOR HIGH SCHOOL STUDENTS IN LHOKSEUMAWE - Andriani Andriani; Meri Hari Yanni; Lia Rista (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2023)
The aim of this research to analyze the improvement of mathematical representation ability students who learning using online mathematics games better than conventionally of junior high school students in Lhokseumawe. The research method is quantitative of quasi experimental method. The population is all grade VIII students at SMPN Negeri 2 Lhokseumawe, SMP Negeri 3 Lhokseumawe, SMP Swasta Sukma Bangsa Lhokseumawe. Sample selection using random sampling class technique. The research instruments used form of representation test and observation sheet. Data analysis begins with a test of normality and homogeneity, the data is analyzed using t-tests of the hypotheses that have been formulated. The results showed that the improve of the mathematical representation ability which taught using online mathematics games better than students taught conventionally of junior high school students in Lhokseumawe